Inhibitory effect of P2X7 receptor antagonists on neutrophil α-defensin-induced interleukin-8 production by human macrophages - Chaly, Yury V.; Nashkevich, Natallia N. (Experimental Biology and Biotechnology, 2017)
Myeloid α-defensins are multifunctional cationic peptides of innate immune system that play an important role in infection, inflammation and human disease. We previously showed participation of HNP 1–3 (human neutrophil peptides 1–3) in regulation of inflammation by stimulation of monocytes and non-monocytic cells to express some cytokines, i. e. сhemokine interleukin-8 (IL-8, CXCL8), in response to HNP, but mechanisms of this induction retained unclear. Using P2X7 receptor antagonists PPADS and KN-62 an effective inhibition of HNP-dependent IL-8 induction in cultures of human macrophages was shown. In contrast to the effect of P2X7 antagonists on, TNFα-induced IL-8 induction was resistant to the action of KN-62. The data suggest the possible involvement of purinergic P2X7 receptor in cell effects of macrophages mediated by neutrophil-released HNP. Our data are useful for understanding of a role of НNР in inflammatory responses and pathological events, as well as for development of tools for neutralization of HNP-mediated detrimental cell effects and improving of diagnostic and therapy methods for HNP-dependent pathologies.
Keywords: α-defensins; P2X7 receptor antagonists; macrophages; interleukin-8 (CXCL8)